Pengaruh Service Quality dan Price Perception Terhadap Customer Loyalty pada Kedai Kopi di Bekasi Timur - Idlal Radhya Andiyana; Dita Puruwita; Prima Andriani (Indo Publishing, 2026)
The rapid growth of the coffee shop industry in East Bekasi has intensified competition, requiring businesses to strengthen customer retention through high service quality and favorable price perceptions. This study aims to examine the effects of service quality and price perception on customer loyalty, both individually and simultaneously. A quantitative approach with a causal associative research design and survey method was employed. Data were collected using a six-point Likert-scale questionnaire from 160 respondents selected through purposive sampling. Respondents were at least 17 years old, resided in or were active in East Bekasi, and had purchased products from local coffee shops. Data were analyzed using IBM SPSS through instrument validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that service quality has a positive and significant effect on customer loyalty (β = 0.294, t = 7.954, p < 0.001), while price perception also has a positive and significant effect (β = 0.356, t = 6.636, p < 0.001). Simultaneously, both variables significantly influence customer loyalty (F = 81.657) and explain 51.0% of its variance. These findings suggest that consistently improving service quality and fostering fair price perceptions are essential strategies for enhancing customer loyalty in coffee shops. The study also contributes empirical evidence to the literature on customer loyalty within the context of local coffee shop businesses.